IMPLEMENTASI METODE ALABAMA (ALFIYAH, BALAGHAH, MANTIQ) DALAM MEMBACA KITAB KUNING DI PONDOK PESANTREN GEDANGSEWU KEDIRI JAWATIMUR - Arianto; Moh. Badrul Munir (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2023)
understanding arabic language is the key to understanding arabic literature. students at salafiah islamic boarding school pondok take years of time to be independent to read the yellow book without the teacher. the alamaba method focusing the three books as requirements for both reading and translation of arabic languages. the books are alfiah, bhalagoh and, mantiq. learning the alamaba method takes two years of santri ability to read and translate the yellow book. The purpose of this study is to describe the application of alabama method in reading the yellow book, advantages and disadvantages in using the method of alabama in Pondok Pesantren Gedangsewu Kecamatan Pare. Data analysis conducted by the author is to reduce the data generated from the informant. Then present the data in accordance with the research objectives systematically. The final analysis provides conclusions by comparing the suitability of the research subject's statement with the basic concepts in the study.The results showed that the method of alabama is a new method of breakthrough to facilitate reading the yellow book. The advantages of the alabama method of the book of alabama is a programmed and printed lesson with a systematic arrangement. Keywords: Alabama method, yellow book